Penerapan Bagian Wasiat Wajibah Terhadap Anak Angkat Dalam Hukum Waris Islam (Perspektif Filosofis) - Muhammad Arafat; M. Roem Syibli (CV Putra Publisher, 2023)
One aspect of concern is Islamic inheritance law. As for matters related to inheritance, namely wills. With the development of Islamic legal thought, the notion of wills has also developed, which is now called obligatory wills, namely rulers or judges as state officials to force or issue obligatory wills for people who have died which are given to certain people under certain circumstances. The research method used in this article is a descriptive method of analysis using a philosophical normative approach. The results of this research are the philosophical basis of adopted children over adoptive parents according to the Compilation of Islamic Law namely in the Indonesian context, the philosophical basis of the applicable law is Pancasila, as the way of life of the Indonesian nation. Then the provision for adopted children to receive 1/3 of the inheritance of their adoptive parents is actually a fair distribution according to legal justice, if the main heirs do not object, while if the heirs object and harm the heirs then the obligatory will is not allowed carried out because it has the potential to harm the offspring of the heir who in fact is the main heir, this is as Raws said, the main interest of justice from laws made by the State is to guarantee the stability of human life.